Pertanggungjawaban Pidana terhadap Pelaku Abortus Provocatus Criminalis (Tindak Pidana Aborsi) - Rini Wulandari (JURNAL RECHTENS, 2019)
Abortion is abortion, the release of the results of conception or fertilization prematurely. Unintentional fetal loss usually occurs in young pregnancies (one to three months). Sometimes a woman's pregnancy can die on its own without an act or intentional act. This is often referred to as "miscarriage" or spontaneous abortion. This often happens to motherswho are still pregnant, due to an unintentional and desirable result or because of an illness.If abortion due to rape is made an exception as a medical reason, then the criteria used as an exception must be absolutely clear and firm, so that it is not misused by irresponsible persons, consequently abortion is rife. Regarding the threat of criminal sanctions for perpetrators of provocatus abortion, in the criminal law (KUHP) it is formulated that there is a criminal threat for those who make an abortion. The Criminal Code does not care about the background or reasons for the abortion.Keywords : abortion, medical reason, criminal law